Multicriteria analysis of technological innovation investments using fuzzy sets - Suder, Asli; Kahraman, Cengiz (Technological and Economic Development of Economy, 2016)
Innovation is the way of transforming the resources of a company through the creativity of people into new resources and wealth. Innovation investments are essential instruments in a company’s competitive productivity and profitability strategy. Evaluation of innovation investments is a multicriteria decision making problem with many conflicting tangible and intangible criteria. Vague nature of this evaluation requires a fuzzy multicriteria methodology. In this paper we propose a fuzzy multicriteria method to evaluate technological innovation investments using eight different criteria. Fuzzy TOPSIS method is used in this evaluation and a sensitivity analysis is given.First published online: 07 Sep 2015